Conformal structure of autonomous Leray–Lions equations in the plane and linearisation by hodograph transform - Duse, Erik (Annales Fennici Mathematici, 2022)
We give sufficient conditions for when an autonomous elliptic Leray–Lions equation in the plane has a conformal structure. This allows the Leray–Lions equation to be linearised in a special form through the hodograph transform.